Structural Design Adapt to Building Mass Forms on Contoured Land - Theresia Pynkyawati; Rini Cahyani (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
Warung Salse is located in Dago Giri Bandung, West Java, is a public building built on contoured ground. The criteria for the material used are light material, do not increase the carrying capacity of the soil and do not cause subsidence. The structure of Warung Salse adjusts to the shape of the building mass and the conditions of the ground contour so that the roof has a multifunctional role as a roof and wall covering with a sloping portal structure, seen from its shape that reaches the ground in front and shrinks behind following the view of the Warung Salse area. The research was conducted using descriptive analysis method, discussing structures with mass associated with mass order theory, mass form, roof structures, columns, beams, and structures on contoured soil. From the final result it will be known the shape of the building mass and the structural model of the contoured soil.